Antenatal urinary retention: Risk factors, treatment, and effect on pelvic floor dysfunction. (April 2022) - O'Leary, Bobby D.; Kelly, Linda; Keane, Declan P.
Abstract: Objective: Physiological changes to the urinary tract begin early in the first trimester and continue throughout pregnancy. Bladder symptoms vary throughout pregnancy and can remain after the puerperium. Antenatal urinary retention is a severe form of pelvic floor dysfunction and research into this topic is sparse. Little is known about the longer-term effects of antenatal urinary retention on pelvic floor dysfunction. This study aimed to establish the incidence of and risk factors for antenatal urinary retention in our population, and whether this had any impact on pelvic floor dysfunction. Study Design: This was a cross-sectional study. Women were included if they were currently pregnant when they required catheterisation—either indwelling, intermittent self-catheterisation or both. The Australian Pelvic Floor Questionnaire was posted to all women. No follow-up reminders were sent and any woman who did not return their questionnaire was recorded as a non-responder. Results: From January 2016 to December 2020, 41 women were identified as needing some form of catheterisation for treatment of antenatal urinary retention. During the same period, 44, 646 women attended the National Maternity Hospital, giving an incidence of antenatal urinary retention of 0.92/1000 pregnancies. Questionnaire results were available for 25 women. One woman did not respond to one question, giving 99.9% complete data. The median (range) total pelvic floor score was 4.6 (0.2–10.7). Risk factors for antenatal urinary retention were identified in ten women. Most women denied any specific bladder symptoms, including difficulty in voiding and a feeling of incomplete emptying. Conclusions: Antenatal urinary retention is an uncommon form of pelvic floor dysfunction and occurs in 1-in-1000 pregnancies. Most women with antenatal urinary retention can be treated with an indwelling catheter for a short period, with only one in four women requiring intermittent self-catheterisation. Retention typically occurs in the late first and early second trimester, and while some risk factors have been identified, most women appear to have an uncomplicated pregnancy before developing acute urinary retention. Reassuringly, long-term pelvic floor dysfunction is minimal in women who experience antenatal urinary retention.